THE EFFECTIVENESS OF GENERATING INTERACTION BETWEEN SCEMATA AND TEXT (GIST) TO TEACH WRITING VIEWED FROM STUDENTSâ INTELLIGENCE - Ningsih, Nuri Ati (English Teaching Journal, 2013)
The research method was quasi experimental research by using simple factorial design 2x2. The population in this research was the second grade students of English Teaching Department of IKIP PGRI Madiun. The writer used cluster random sampling to get the sample. It consists of 60 students which were divided into two classes, II D consisting 30 students as a control class and II B consisting 30 students as an experimental class. The instruments used to collect the data were writing test to get the score of writing skill. Documentation was used to get the data of studentsâ intelligence. Before the instruments were used, the tryout was done to know the validity and readiability of instruments. The writer analyzed the data in term of their frequency distribution, normality, and homogeneity. Then, the data were analyzed by using multifactoral analysis 2X2.The findings in this research lead to some conclusions: (1) GIST is more effective than DI for teaching writing; (2) The students having high intelligence have better writing skill than the students having low intelligence; and (3) There is an interaction between teaching strategies and studentsâ intelligence for teaching writing. The effect of teaching strategies on the studentsâwriting skill depends on the studentsâintelligence.Key words: Teaching, Writing, GIST, Direct Instruction, Intelligence.